Merrifield Resin Supported Ionic Liquids: Catalytic Applications in Organic Synthesis - Aggarwal, Ayushi; Singh, Avtar; Chopra, Harish K. (Current Organic Chemistry, 2023)
Ever since their discovery, Ionic Liquids have raised great interest in organic transformations ranging from solvents to catalytic entities. These belong to a class of nonmolecular compounds composed of ions having curiously low melting points. In the last few years, the Supported Ionic Liquids have drawn the attention of researchers and chemists due to their advantages over homogeneous catalysis. The most commonly used support for immobilized ionic liquids is polymeric. Due to its efficient recovery, reusability and chemical inertness, Merrifield resin can be considered an excellent solid support for ionic liquids. The present review summarizes the synthesis and application of Merrifield Resin Supported Ionic Liquids (MRSILs). The MRSILs can be synthesized by the immobilization of amines like ammonium, choline, imidazolium, DABCO, DMAP, pyridine, and many other functionalized precursors. Additionally, these MRSILs play an incredible role in the field of catalysis, where both metal-free and metal-containing MRSILs are embodied as a catalyst.
Keywords: desulfurization